Domestic hygiene: possible link between antibiotic resistant salmonella and e.coli and resistance to household antimicrobial agents - Thorrold, Catherine Ann (My University, 2006)
Inappropriate use of antimicrobial agents has been shown to select for organisms with resistance mechanisms (eg. efflux pumps), which could lead to the development of antibiotic resistance. The objective of this study was to investigate a possible link between antibiotic resistant gastrointestinal pathogens and reduced susceptibility to anti microbial agents found in commonly used household disinfectants. Tetracycline and ofloxacin resistant and sensitive Salmonella and E.coli species were isolated from fresh poultry and clinical samples. Ethidium bromide accumulation assays were performed to assess the presence of active efflux pumps. Using spectrophotometric accumulation assays, the extrusion of the active components of commercial household agents by the efflux pumps was tested. To determine changes in the efficacy of these products, in-use disinfectant testing was performed. Active efflux pumps and extrusion of the active ingredients was observed in the resistant but not in the sensitive organisms. When the household products were used at the recommended concentrations, a significant reduction of both resistant and sensitive bacteria was observed after the in-use disinfectant testing procedure. However, if the household products were used at concentrations below the recommended concentration, the resistant bacteria were not eliminated as efficiently as the sensitive bacteria.
Student Number : 9906314R - MSc dissertation - School of Pathology - Faculty of Science
Keywords: antimicrobial agents; efflux pumps